Working from home and firm resilience to the COVID‐19 pandemic. Issue 3 (17th July 2022) - Ge, Chunmian; Huang, Hanwei; Wang, Zhiqiang; Jiang, Junhui; Liu, Chang
Abstract: The COVID‐19 pandemic has disrupted firms' operations. To cope with the crisis, many firms have allowed their employees to work from home (WFH). We examine whether a firm's WFH capacity has increased its resilience during the pandemic. We test the hypotheses using a unique data set that combines listed firms' financial statements, supply chain partners, and job postings on a leading online platform that provides hiring services. We find that imposing COVID‐19 anti‐contagion policies on firms and their suppliers or customers significantly increases their operating revenue volatility, slows their recovery, and has repercussions on their supply chains. WFH enhances firms' resistance capacity by reducing the effect of COVID‐19 on their operating revenue volatility and disruptions to their supply chain partners; however, it also decreases their recovery capacity by extending the time taken to return to normal. Firm attributes, along with workers' occupations, education, and experience, have an impact on the effect of WFH on firm resilience. This study enhances our understanding of shock transmission across supply chains and WFH as a source of firm resilience. Highlights: Measures of Work‐from‐Home (WFH) capacity are developed for Chinese listed firms based on their online job postings. Exploring the variation of policies against COVID‐19 across Chinese cities, we find these policies increased listed firms' operating revenue volatility, slowed their recovery, and generated repercussions on their supply chains. WFH acted like a double‐edged sword: on the one hand, it enhanced firms' resistance capacity by reducing the effect of COVID‐19 on their operating revenue volatility and disruptions to their supply chain partners; on the other hand, it decreased their recovery capacity by extending the time taken to return to normal.